1969
DOI: 10.1128/aem.18.5.798-805.1969
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Sporulation, and Germination of Clostridium perfringens in Media of Controlled Water Activity1

Abstract: Requirements in terms of water activity (a,) for the growth, sporulation, and germination of Clostridium perfringens were determined. Strain A48 was used in all phases, and in addition either NCTC 8239 or NCTC 8797 was used for growth, sporulation, and germination studies. The desired a, of the test media was obtained by the addition of one of three solutes: glycerol, sucrose, or sodium chloride. The freezing point depression method was used to determine the a,. The basal medium for growth and germination was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The significantly greater inhibition of growth by NaCl or sucrose as compared with that for glycerol at various a, values and over a temperature range at 0.98 a, has been reported for Ps.Juorescens and other bacteria (Marshall et al 1971;Kang et al 1969), yeasts (Brown & Simpson 1972;Horner & Anagnostopoulos 1973) and fungi (Charlang & Horowitz 1971;Horner & Anagnostopoulos 1973). However, the greater inhibition by NaCl than glycerol at equivalent a, only applies to salt-sensitive microorganisms (Marshall el ul.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significantly greater inhibition of growth by NaCl or sucrose as compared with that for glycerol at various a, values and over a temperature range at 0.98 a, has been reported for Ps.Juorescens and other bacteria (Marshall et al 1971;Kang et al 1969), yeasts (Brown & Simpson 1972;Horner & Anagnostopoulos 1973) and fungi (Charlang & Horowitz 1971;Horner & Anagnostopoulos 1973). However, the greater inhibition by NaCl than glycerol at equivalent a, only applies to salt-sensitive microorganisms (Marshall el ul.…”
Section: Discussionmentioning
confidence: 99%
“…For example, halophiles and osmophiles require significant concentrations of solutes for rapid growth. However, for most types of micro-organisms, reductions in a, of the surrounding environment decreases their growth rate (Scott 1957; Pirt 1 9 7 9 , the respiration rate (Christian 1955;Brown 1975), enzyme activity (Baxter & Gibbons 1954: Brown & Simpson 1972, sporulation (Kang et al 1969) and toxin production (Troller 1973). The lowering of a, also increases the permeability of the cell membrane (Charlang & Horowitz 1974) and affects the intracellular composition (Christian & Waltho 1964;Brown 1974).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for this organism the a, requirements for sporulation seem to be very similar to the requirements for vegetative growth. Kang et al (1969), using NaCI, glycerol and sucrose as controlling solutes found that spore production by CZ. perfringens required a significantly higher a, than did growth.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally advanced that the minimal aw that permits sporulation is similar to or slightly above that for growth, while spore germination may occur even at lower aw(Baird-Parker and Freame 1967 ; Ingram and Kitchell 1967; J . N. SOFOS Kang et al 1969;Troller 1973;1980 Jakobsen andSperber 1983).…”
Section: Microorganismsmentioning
confidence: 99%